Recruitment & selection - Denny, Richard; Lake, Nick; Turner, Barry; Gawith, Paul ([S.l.] : Man Management Ltd. [production company] ; Kuala Lumpur : First Training [distributor])
Disscused about the selection people in certain company. Tarining for a recruiting and hiring people
Camera, Mark Lipscomb ; sound supervisor, Bill Cadman ; lighting director, Nigel Fisher
Keywords: Employees -- Recruiting; Employment interviewing; Communication in management